PENYULUHAN PENGOLAHAN SELAI BAGI SISWA SMK NEGERI 1 BAWEN KABUPATEN SEMARANG - Larasati, Dewi; Putri, Aldila Sagitaning; Sani, Elly Yuniarti (Fokus ABDIMAS, 2022)
This community service activity is partnered with SMK Negeri 1 Bawen, Semarang Regency. The partner location is in Bawen District, Semarang Regency. Our target is students majoring in Agribusiness Processing of Agricultural Products (APHP) at SMK Negeri 1 Bawen who are accompanied by their teachers. One of its visions is to educate and train students to be skilled, independent and able to develop themselves in the competence of Agribusiness Processing Agricultural Products. So that counseling is needed about the knowledge of various kinds of agricultural products, while the subject matter given does not cover all agricultural products, one of which is tomatoes. The solution method is to provide counseling about processed tomato jam and the practice of making it for students of SMK Negeri 1 Bawen. The results of this activity can improve the knowledge and skills of the students of SMK Negeri 1 Bawen so as to increase their competence. Keywords: processing, tomato jam, students of SMK Negeri 1 Bawen